Stanton Convention Centre. Issue 1 (4th January 2016) - Anderson, Joe; Williams, Susan K.
Abstract : Synopsis: Used hypodermic needles were found in Stanton Convention Centre. The Centre's department heads suggested installing secure needle receptacles. June Patterson, General Manager, quickly learned this was a divisive issue. Heated arguments focussed on two opinions: first, the Centre owed employees a safe working environment and needles constituted a significant risk to safety. Second, other department heads believed that presence of needle boxes would diminish customers' perceptions of the Centre. According to one, "You wouldn't find needle boxes in nice restaurants or golf courses." Having promised a decision by the next meeting, Patterson mulled the question over and wondered how to proceed. Research methodology: This case was written based on information obtained in interviews with the manager described in the case. The manager's name, the name of the organization, and the city where it is located have all been disguised. Relevant courses and levels: The authors use this case as the first contact with cases for our incoming MBA cohort in the summer pre-session to acquaint them with the basics of case analysis. However, this compact case could be used in many management courses, graduate or undergraduate, to illustrate difficulties in management decision making for different stakeholder groups. Theoretical bases: The concepts most central to our discussions of the case are management decision making and the influences of diverse stakeholder opinions on those decisions.